(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The aim of this essay is to demonstrate how, starting from a continuous reconfiguration of ecological patterns, Homo sapiens has performed a transaction of the architectures that allow him to relate to his own conspecifics and to constantly changing contexts. This transaction, which has been realised in particular by the refinement of his artefacts and by a new understanding of these, creates, in fact, new ontological levels that are destined, in turn, to following transformations. More precisely, the interaction between individual and environment has produced, throughout the evolutionary history of Homo sapiens, a “creative bond” that has remodelled the very concept of living in (and reacting in) the world. The creative evolution that accompanies the history of the modern man is one of the most powerful and versatile types of “grammar”, which paves the way for new task-scapes, redefines boundaries and ways of interaction between “body” and “environment” but, above all, makes the creation of increasingly more user-friendly communicative niches possible today, creating symbolic flows that are increasingly less infused in biological matrices. In other words, the interactional loop between individual and environment creates the cognitive equivalent (Clarck, 2004) of Dawkins’ Extended Phenotype (1982) that, along with a spatial constraint of the physical world, provokes an expansion in the relationship among agents, culture and social networks at the same time.